2016
DOI: 10.1038/srep33554
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in gastric lamina propria of the Chinese giant salamander, Andrias davidianus

Abstract: In this study, we attempt to identify gastric telocytes (TCs) of the Chinese giant salamander Andrias davidianus, by light microscopy, immunohistochemistry and transmission electron microscopy (TEM) methods. Toluidine blue staining showed TCs with one to two very thin and long telopodes (Tps) that were located in gastric lamina propria. Tps had characteristic structures, including podoms, podomers and dichotomous branching. Immunohistochemistry showed the existence of CD34+/PDGFRα+ TCs with moniliform Tps in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In the current study, all TCs in the efferent ductules of camel were CD34, VEGF and vimentin positive. Camel TCs express CD34 similar immunophenotype of TCs in other mammalian species 42 as well as avian species 59 , reptiles 50 , amphibians 60 and clitellates species 2 . CD34/PDGFR-α has been identified as a specific marker for TCs 61 .…”
Section: Discussionmentioning
confidence: 70%
“…In the current study, all TCs in the efferent ductules of camel were CD34, VEGF and vimentin positive. Camel TCs express CD34 similar immunophenotype of TCs in other mammalian species 42 as well as avian species 59 , reptiles 50 , amphibians 60 and clitellates species 2 . CD34/PDGFR-α has been identified as a specific marker for TCs 61 .…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, TCs secrete extracellular vesicles that play an important role in supporting tissue repair/regeneration and nurse function, intercellular signaling, cell differentiation [16], homeostasis maintenance, and transport and release of lipids, proteins, as well as nucleic acids, in order to meet the target tissue requirements [17][18][19][20][21]. This communication is achieved by releasing the microRNA-filled extracellular vesicles from TCs/Tps to regulate cell functions [22].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural evidences of telocytes in ileum were found in the Chinese giant salamander Andrias davidianus (amphibian; Zhang et al, ). In the reptile Pelodiscus sinensis , known as Chinese soft‐shelled turtle, novel interstitial cells were found in the testis of the males (Yang et al, ), and similar cells were observed in the uterus of the oviduct in the female these animals (Ullah et al, ).…”
Section: Discussionmentioning
confidence: 99%